2021
DOI: 10.1590/0102-33062020abb0414
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic aid arising from pollen grains of Cestrum L. and Solanum L. (Solanaceae): differences in ornamentation and aperture

Abstract: Solanaceae is represented by herbs, shrubs, trees and climbing plants and has cosmopolitan distribution, with a large number of native species in the Neotropical region. This study aimed to characterize the pollen morphology of ten species of Solanaceae (especially species of Cestrum and Solanum) from Cerrado forest fragments in Brazil, in order to contribute to the palynology, taxonomy and conservation of degraded areas. Pollen grains were acetolysed, measured and photographed using light and scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The pollinic morphology and antimicrobial activities of 12 Cucurbitaceae species originating from the floristically rich desert region of Saudi Arabia were investigated, revealing intriguing insights into the stances (Fatmi et al, 2020). Qualitative data on pollen dimensions and apertural diameter variability were also discovered to be significant in angiosperm authentication (Landi et al, 2022). In order to identify the higher degree of pollination efficiency and improve trade-offs, our findings contribute to a better understanding of the effect that climate gradients have on the variability in pollen morphology among Cucurbitaceae species that inhabit arid dry lands of Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…The pollinic morphology and antimicrobial activities of 12 Cucurbitaceae species originating from the floristically rich desert region of Saudi Arabia were investigated, revealing intriguing insights into the stances (Fatmi et al, 2020). Qualitative data on pollen dimensions and apertural diameter variability were also discovered to be significant in angiosperm authentication (Landi et al, 2022). In order to identify the higher degree of pollination efficiency and improve trade-offs, our findings contribute to a better understanding of the effect that climate gradients have on the variability in pollen morphology among Cucurbitaceae species that inhabit arid dry lands of Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, manifold palynological studies have been carried out in the Cerrado forest fragment areas, especially in the State of São Paulo (Brazil). Families such as Bignoniaceae (Souza and Gasparino 2014;Souza et al 2019), Malpighiaceae (Belonsi and Gasparino 2015), Rutaceae (Dutra and Gasparino 2018), Amaranthaceae and Araliaceae (Landi and Gasparino 2018), Sapindaceae (Bellonzi et al 2020), Fabaceae (Soares et al 2021(Soares et al , 2022, Rubiaceae (Dutra et al 2020), Solanaceae (Landi et al 2021), Malvaceae (Lopes et al 2022) and Boraginaceae (Landi et al 2022) have been studied. These studies showed variations in the pollen unit, polarity, shape, amb, size, aperture and ornamentation of the pollen grains of these families, contributing to the taxonomic knowledge on and the conservation of these species in the forest area.…”
Section: Introductionmentioning
confidence: 99%